Synthesis and characterization of oxides produced by high temperature corrosion on grade 300 and 350 maraging steels - Cerra Florez, Mauro Andres (2021)
The aging heat treatments in maraging steels are fundamental to achieving their excellent mechanical properties and, in some applications using oxidation surface treatments lead to induce a superficial layer formed by iron spinel which in some cases it can be protective. In this research, an exhaustive study of the characterization and mechanical properties of the grade 300 and 350 maraging steels was performed. Trying to produce a spinel-like oxide film on these steels during the aging heat treatment at 485 ºC, a novel procedure with particular conditions based in different steps combining time, temperature, atmosphere and leakage were developed. Four applications of the procedure were made using Air, O2, CO2 or N2 in the first steps, and using similar conditions of steam, helium and N2 atmospheres in the rest of the procedure. Afterwards, the layer produced in all the procedures was microstructural and mechanically characterized by means of advanced characterization techniques at the micro- and submicrometric length scale in order to highlight information related to the generated oxide layers. Differences between the oxides produced in all the conditions were found, such as roughness, thickness, and the quantity of the superficial heterogeneities (ridges, valleys, cracks, porosity and peeling), but the most important results area related to the chemical composition and the adherence of the oxides. The results of the procedure using air and O2 atmospheres showed (in both steels) a non-homogeneous mix oxide formed by magnetite (Fe3O4), nickel ferrite (NiFe2O4), cobalt ferrite (CoFe2O4), MoO3, TiO2 and a particularly important quantify of hematite (α-Fe2O3). The oxide produced using CO2 atmosphere was formed by TiO2, MoO3, hematite and the spinel CoFe2O4 being the latter one the majority compound. And using the N2 atmosphere it was found that the oxide thickness (in both steels) was made up of the spinel’s Fe3O4 and CoFe2O4 (with amounts was close to ~ 85%), MoO3, TiO2 and no Hematite was found.